2022
DOI: 10.1002/ird.2729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field treatment of broad bean seeds and irrigation water on the growth and yield of plants

Abstract: Techniques for the magnetic treatment of water have become one of the most common practices for improving the agricultural sector. The effects of alternating magnetic field treatment of broad bean (Luz de Otoño) seeds and irrigation water on plant growth and yield were investigated under pot conditions. The magnetic treatments included (i) magnetically treated seeds (MTS), (ii) magnetically treated irrigation water (MTIW), and (iii) no magnetic treatment of both seeds and irrigation water, which were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the combination between the MT of the seeds and the N-fertilizer significantly increased the N availability in soil and uptake by groundnut seeds. The interactive significant effect of the MT of the seeds and the N-fertilizer is strongly reflected in the estimated yield and yield parameters in tables 4 and 5 (El-Basioni et al (2015), Hafeez et al (2023), Bairwa et al (2023), Altalib et al (2022), Nile et al (2022)). As well, it showed an almost significant effect on the uptake of the P and K nutrients along with the Na/K ratio in the seeds and/or the straw (Tables 6 and 7).…”
Section: Discussionmentioning
confidence: 97%
“…However, the combination between the MT of the seeds and the N-fertilizer significantly increased the N availability in soil and uptake by groundnut seeds. The interactive significant effect of the MT of the seeds and the N-fertilizer is strongly reflected in the estimated yield and yield parameters in tables 4 and 5 (El-Basioni et al (2015), Hafeez et al (2023), Bairwa et al (2023), Altalib et al (2022), Nile et al (2022)). As well, it showed an almost significant effect on the uptake of the P and K nutrients along with the Na/K ratio in the seeds and/or the straw (Tables 6 and 7).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies aim to understand the mechanisms of using water treated with magnetic fields [27,32]. For Populus [33], eggplant [34], wheat [35], and lettuce crops [36], it was found that it provided a reduction in the effects caused by water stress conditions. In addition, studies with germination in tomatoes [37,38] and wheat [39] in saline conditions showed greater development when irrigated with treated water.…”
Section: Introductionmentioning
confidence: 99%